Developing a Culture to Facilitate Research Capacity Building for Clinical Nurse Consultants in Generalist Paediatric Practice - Lesley Wilkes; Joanne Cummings; Nicola McKay (Nursing Research and Practice)
This paper reports a research capacity building exercise with a group of CNCs practicing in the speciality of paediatrics in New South Wales (NSW), Australia. It explores the first step in building a research culture, through identifying the research priorities of members of the NSW Child Health Networks Paediatric Clinical Nurse Consultant group, and this forms the major focus of this paper. A nominal group technique (NGT) was utilised with sixteen members to identify research topics for investigation which were considered a priority for improving children's health care. The group reviewed and prioritised 43 research topics in children's health which were identified in the literature. As a result of conducting this research prioritisation exercise, the group chose two research topics to investigate: reasons for children representing to the Emergency Department and a comparison of the use of high-flow and low-flow nasal prongs in children with bronchiolitis. The research team will continue to mentor the nurses throughout their research projects which resulted from the NGT. One bridge to leadership development in enhancing patient care is translating knowledge to practice and policy development. This study leads the way for a group of CNCs in paediatric nursing to combine their research capacity and influence clinical knowledge.